Gendered Access toSocial Capital: Challenges Faced by Women Academics in Punjab (Pakistan) (Journal of Asian Development Studies, 2026)
Pakistan is a developing country, continuously struggling to improve women's status in society. Scholarship revealed that social capital is a crucial aspect in professional advancement in academia. Associations with different groups and interpersonal connections are crucial in defining social position and access to career-related information and sources. The present study aims to explore the gendered access to social capital and the challenges women face in linking, bridging, and bonding social capital. For deep insight, 30 in-depth interviews were conducted by using a purposive sampling technique. To analysethe experiences, thematic analysis was used to identify themes from the collected data. The findings highlighted patriarchy as a key factor in restricted access to career-enhancing social networks. Enduring gender norms are influencing professional trajectories of female academicians, and the intersection of family and professional role pressure is limiting their ability to establish social ties, networking, and other groupings that collectively establish their social capital, which reduces the inflow of new ideas and input into and in turn affect women's career advancement and performance in the workplace